1993
DOI: 10.1111/j.2042-3306.1993.tb02941.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stabling on bronchoalveolar cells obtained from normal and COPD horses

Abstract: Summary Bronchoalveolar lavages (BAL) were performed before and after 3 weeks of housing in 5 horses suffering from COPD and 5 normal horses. In the two groups, the total number of cells recovered remained unchanged after stabling. The most common cell populations in BAL fluid of control animals were alveolar macrophages (46.4%) and lymphocytes (44.9%). The percentage of neutrophils increased after stabling from 8.7% to 27.6%. In COPD horses, lymphocytes predominated (40.7%) in animals at pasture with neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
65
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 23 publications
12
65
0
5
Order By: Relevance
“…A previous study found that the mean duration of IAD incidents was significantly higher for horses kept in an environment where dust loading was higher and ventilation was less well regulated (10). Respirable endotoxin, measured at the level of horses' nares, has been shown to be correlated with levels of neutrophilic inflammation in similar racehorses in Australia (31), and stabling in itself can cause some inflammation in airways (27,50). However, direct comparison of these factors was outside the objectives of this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found that the mean duration of IAD incidents was significantly higher for horses kept in an environment where dust loading was higher and ventilation was less well regulated (10). Respirable endotoxin, measured at the level of horses' nares, has been shown to be correlated with levels of neutrophilic inflammation in similar racehorses in Australia (31), and stabling in itself can cause some inflammation in airways (27,50). However, direct comparison of these factors was outside the objectives of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on individual agents suggest the possible involvement of viral infection (59), bacterial infection (10,14,16,42,43,56), and environmental loading of the respiratory system (10,27,33,50), as well as dysregulation of inflammatory processes (6). Individual bacteria commonly reported from cases include Streptococcus zooepidemicus (10,14,16,42,56), Streptococcus pneumoniae (14,16,56), Actinobacillus spp.…”
mentioning
confidence: 99%
“…Interestingly, despite years of previous antigenic stimulation, there was no polarization of lymphocytes to a T H 2-type of response in horses with COPD during clinical remission [40]. Typically, neutrophils are recruited to the lungs of horses with COPD and further add to the inflammatory process [24,57,128]. There is evidence that T H 2 cytokines are involved in the modulation of the inflammation from a neutrophilic to an eosinophil-induced type of inflammation [24,57].…”
Section: El Thackermentioning
confidence: 99%
“…There are also various analyses aimed to examine cellular and non-cellular immunologic components. Diagnosis of airway inflammation in horses is determined based on a combination of history, clinical examination, endoscopy and, in many instances, bronchoalveolar lavage (BAL) cytology (Derksen et al, 1985;Tremblay et al, 1993). Results from pulmonary function tests are used in research and for clinical purposes for disease monitoring and in grading of disease severity (Derksen et al, 1985).…”
Section: Investigation Of Horsesmentioning
confidence: 99%